A simulation study of switched reluctance motor (SRM) driven using binary modulated excitation / Samsudin Karsan - Karsan, Samsudin (2014)
The switched-reluctance (SR) motor excels at the very low end of the speed-being able to provide high torques with excellent dynamic capability, and at very high speeds due to its robust rotor. SR systems are used in clothes washers, food processors, vacuums, power tools and other high-performance applications. The SR motor is a variable speed machine, many control schemes such as those employing PID, neural and fuzzy algorithms have been proposed.